Energy Efficient Innovations and Market Acceptance: A Revealed Preference Approach - Chikandiwa, Christopher Tarisayi (Acta Universitatis Danubius. Œconomica, 2025)
Green energy innovations such as microgeneration technologies could be the vital cog in combating climate change and its impact, mainly due to their non-damaging effect on the environmental ecosystem. Previous studies on market acceptance of housing energy efficiency are very scant in the African region, and little is known about the acceptance and adoption of green energy technologies in residential spaces in the African region. Therefore, this article seeks to establish the extent of market acceptance of energy-efficient innovations in the residential sector, particularly in South Africa. The revealed and implied priority approach was employed in a sample of housing advertisements in KwaZulu-Natal, a province of South Africa. The study’s findings show that the market does not prioritise energy-efficiency innovations. Specifically, the enquiry showed that energy-efficiency innovations are characteristic of the local housing stock in the province. Still, participants in the housing property market do not seem to value them. This article is valuable as it not only conceptualises and demonstrates the applicability of the revealed approach and the implied priority methods in portraying the actual choices made by individuals with regard to energy efficiency technologies, but it also suggests some strategies as an effort to improve green energy innovation adoption by homeowners in the province.